PHOTOSYNTHETIC ACTIVITY OF PLANTS SPRING CAMELINA SATIVA, DEPENDING ON THE PROCESSING METHODS OF CULTIVATION - Стельмах, О. М.; Григорів, Я. Я.; Максимів, Т. О. (Scientific Progress & Innovations, 2014)
The results of studies on the impact of technological methods of cultivation on the growth dynamics of leaf area and photosynthetic capacity of crops formation. The research found that the highest rates of leaf surface area obtained for the first sowing in spring Camelina sativa flowering phase. Established that fertilization had a significant effect on the leaf surface area of spring Camelina sativa according to rate of photosynthetic capacity.